2019
DOI: 10.1371/journal.pone.0222414
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical integrated and segregated processing in the functional brain default mode network within attention-deficit/hyperactivity disorder

Abstract: The hierarchical modular organization of functional networks in the brain is crucial for supporting diverse cognitive functions. Functional disorders in the brain are associated with an abnormal hierarchical modular organization. The default mode network (DMN) is a complex dynamic network that is linked to specialized cognitive functions and clinically relevant information. In this study, we hypothesize that hierarchical functional segregation and integration of the DMN within attention-deficit/hyperactivity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…
Subnetworks of the brain are hierarchically organized and can be defined across multiple spatial scales ( Meunier et al, 2010 , Sporns, 2013 ). Therefore, the spatial characterization of network organization and “efficiency” in MS might be improved using multilevel subnetwork definitions ( Akiki and Abdallah, 2019 , Fan et al, 2019 , Wang et al, 2021 ). Future studies should take this into account, which could lead to a better understanding and resolve some of the discrepancies related to the local network changes in MS patients with cognitive impairment.
…”
Section: Network Organization: a Loss Of Efficiency In Ms?mentioning
confidence: 99%
“…
Subnetworks of the brain are hierarchically organized and can be defined across multiple spatial scales ( Meunier et al, 2010 , Sporns, 2013 ). Therefore, the spatial characterization of network organization and “efficiency” in MS might be improved using multilevel subnetwork definitions ( Akiki and Abdallah, 2019 , Fan et al, 2019 , Wang et al, 2021 ). Future studies should take this into account, which could lead to a better understanding and resolve some of the discrepancies related to the local network changes in MS patients with cognitive impairment.
…”
Section: Network Organization: a Loss Of Efficiency In Ms?mentioning
confidence: 99%
“…Functional segregation, together with the integration between anatomically distant regions, underlies the typical developmental pattern of the large-scale functional networks (Fair et al, 2007, 2009). Reduced between-network segregation has been previously reported not only in children with ADHD (Mills et al, 2018), but also in adults with the disorder (Fan et al, 2019). Our study reveals that the brain of patients with ADHD shows features that resemble those of a more immature brain, and suggests that, at least when the disorder has never been medicated and persists into adulthood, those features do not remit with age.…”
Section: Discussionmentioning
confidence: 95%
“…Opposite to the child studies, He and colleagues (2022) observed decreased segregation in an adult ADHD group, in relation to NT controls, globally in the brain, as well as locally in the left parahippocampal gyrus and right supplementary motor area and "modules" in central and left-sided frontal areas. In functional connectivity studies, both increased (e.g., Fan et al, 2019;Pretus et al, 2019) and decreased (e.g., Lin et al, 2018) segregation in ADHD have been found. Contrary to the studies described above, a study by Hearne and colleagues (2021) found no differences in DW-MRI data between adults with and without ADHD.…”
Section: Introductionmentioning
confidence: 98%
“…In the temporal and inferior parietal cortex, weaker connectivity was further associated with more severe ADHD symptoms and stronger connectivity in the right putamen was associated with hyperactivity/impulsivity symptoms. Wang and colleagues (2021) reported that adults with ADHD have lower global network efficiency and smaller density of 'rich-clubs' than NT controls in several cerebral and subcortical structural hub nodes, both results reflecting decreased integration, a phenomenon mirrored in adult functional connectivity studies (e.g., Fan et al, 2019;Pretus et al, 2019). Opposite to the child studies, He and colleagues (2022) observed decreased segregation in an adult ADHD group, in relation to NT controls, globally in the brain, as well as locally in the left parahippocampal gyrus and right supplementary motor area and "modules" in central and left-sided frontal areas.…”
Section: Introductionmentioning
confidence: 99%